Bengkuang as an Alternative for Hypoestrogen Problems in the Reproductive System - Mayasari Putri Ardela; Meirna Eka Fitriasnani; Putri Erika Kulistiyani (Journal Of Nursing Practice, 2025)
Background: Hypoestrogenism is a condition characterized by a deficiency of the hormone estrogen. This condition is commonly experienced by women who are menopausal or those using hormonal contraceptives like Depot Medroxyprogesterone Acetate. Exposure to this synthetic progesterone can suppress the production of estrogen, leading to a decrease in the expression of estrogen receptors. One alternative to overcome the problem of hypoestrogenism is the use of natural ingredients known as phytoestrogens, which are chemically and functionally similar to estrogen. Bengkuang is known as one of the sources of phytoestrogens. Purpose: This study aims to assess the impact of bengkuang ethanol extract on estrogen levels and the expression of estrogen receptor beta in a hypoestrogenic rat model exposed to DMPA. Methods: This experimental study involved 25 rats, which were divided into five groups. One group served as the negative control and did not receive DMPA or Bengkuang extract, while the four treatment groups were administered DMPA at a dose of 2,7 mg every three days, repeated four times. Three of the treatment groups received Bengkuang extract at varying doses. The data were analyzed using a one-way ANOVA test. Results: The findings indicated significant differences (p < 0,05) in estrogen levels and the expression of estrogen receptor beta. Conclusion: Administration of bengkuang extract can enhance the female reproductive system with low estrogen levels.